Integrating Technology into Problem-Based Learning: A Practical Implementation - Taranthy, Putu Lydwin Githa; Juniarta, Putu Adi Krisna; Ana, I Ketut Trika Adi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
In alignment with the Kurikulum Merdeka, Problem-Based Learning (PBL) has been widely promoted as a strategy to enhance critical thinking, collaboration, and problem-solving skills. The integration of technology into PBL further strengthens its potential by providing multimodal resources and interactive opportunities for learners. However, limited research has examined students’ readiness to participate in technology-enhanced PBL within Indonesian EFL classrooms, creating a gap in understanding the feasibility of its implementation. This study aims to investigate how technology integration is applied in PBL and to evaluate students’ readiness to engage in this approach. An exploratory sequential mixed-methods design was employed. Participants included one English teacher and ninety-seven tenth-grade students from three classes. Instruments consisted of observation sheets, field notes, and a readiness questionnaire adapted from Dalton and Gottlieb’s framework. Data collection began with classroom observations to identify teacher practices, followed by the administration of the questionnaire to measure student readiness. Qualitative data were analyzed using Miles and Huberman’s model, while quantitative data were analyzed descriptively. The findings revealed that the teacher successfully integrated videos and PowerPoint slides across PBL stages, supporting contextual understanding and engagement. Nevertheless, students demonstrated only moderate readiness across effort, willingness, and technological capacity.